Biorefinery potential of coffee silverskin: Composition and applications - Elena M. Anchugova; Elena V. Udoratina; Elena G. Kazakova; Anastasiia O. Nosova; Mayya V. Uspenskaya; Tatiana N. Shchemelinina (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Achievements in biotechnology have paved the way for the efficient utilization of agricultural and industrial waste, presenting potential opportunities for sustainability and resource optimization. One such waste that has been studied is coffee silverskin (CS), the only waste generated during the coffee roasting process. This paper aims to analyze the potential of CS for biorefinery and explore its value enhancement through biotechnology.